Nonverbal communication at the ecolinguistic grassroots - Craig Frayne (Russian Journal of Linguistics)
In the Lebenswelt of everyday communication, meaning emerges from the interplay of verbal and nonverbal semiosis. While textual discourse analysis offers valuable insights, the richness and complexity of human communication come to the fore when considering communication in its entirety, including nonverbal elements. This paper aims to move beyond theoretical analysis and support real-world organizing efforts, offering a more comprehensive understanding of the human-environment relationship and its implications for environmental justice. It argues for integrating nonverbal analysis into ecolinguistic praxis, particularly in engagement with communities and civil society, or the ecolinguistic ‘grassroots.’ However, there is a gap in existing ecolinguistic scholarship regarding frameworks for this integration. To address this, the paper presents a multilevel methodology based on eight hours of audio and video recordings, which capture different perspectives on mining operations and proposed developments. These include interviews, documentaries, and recordings from ‘town hall’ meetings from YouTube recordings uploaded between approximately 2007 and 2018. Analysis of facial expressions and gestures reveals distinct cognitive responses at different thematic levels of discourse (ecological, cultural, socioeconomic). This paper demonstrates how such findings have important implications for practitioners engaging with working-class communities impacted by environmental change. As nonverbal research increasingly focuses on human-computer interaction and artificial intelligence, this study advocates for nonverbal analysis as humanistic inquiry, emphasizing meaning-centered approaches that draw from the embodied nature of human interaction to foster empathic understanding and more effective organizing within communities.